3, 3′- DIINDOLYLMETHANE ENHANCES CHEMOSENSITIVITY OF MULTIPLE CHEMOTHERAPEUTIC AGENTS IN PANCREATIC CANCER - Banerjee, Sanjeev (2009)
Clinical management of pancreatic cancer (PC) is a major problem, which is in part due to both de novo and acquired resistance to conventional therapeutics. Here, we present in vitro and in vivo preclinical evidence in support of chemo-sensitization of PC cells by DIM, a natural compound that can be easily obtained by consuming cruciferous vegetables. DIM pretreatment of PC cells led to a significantly increased apoptosis (p<0.01) with suboptimal concentrations of chemotherapeutic agents (cisplatin, gemcitabine and oxaliplatin) compared to monotherapy. It is known that resistance to chemotherapy in PC is associated with constitutively activated NF-κB, which becomes further activated by chemotherapeutic drugs. Our data provide mechanistic evidence for the first time showing that DIM potentiates the killing of PC cells by down-regulation of constitutive as well as drug induced activation of NF-κB and its downstream genes (Bcl-xL, XIAP, c-IAP, survivin). Most importantly, using an orthotopic animal model, we found reduction in tumor size (p<0.001) when DIM was given in combination with oxaliplatin compared to monotherapy. This was accompanied by loss of phospho p-65, down-regulation of NF-κB activity and its downstream genes (Bcl-xL, survivin and XIAP), which correlated with reduced cell proliferation (as assessed by Ki-67 immunostaining of tumor specimens) and evidence of apoptosis (as assessed by PARP cleavage and TUNEL staining). These results provide strong in vivo evidence in support of our hypothesis that DIM could abrogate chemotherapeutic drug (cisplatin, gemcitabine and/or oxaliplatin) induced activation of NF-κB, resulting in the chemo-sensitization of pancreatic tumors to conventional therapeutics.